PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PENUMPANG PADA PT.KERETA API INDONESIA (PERSERO) SUB. DIVRE IV TANJUNG KARANG - mei endang (e-JKPP, 2016)
Competition transportation services to achieve or accomplishment with good quality services by providing quality products, aims to be ahead of the competition in the field of transportation services. This study aimed to identify the influence of the quality of service and product quality to achieve passenger satisfaction.This study uses a quantitative approach is data in the form of numbers. The study was conducted in Indonesian Railways Corporation (Limited Company) Sub.Divre IV Tanjung Karang. The method used simple linear regression and multiple linear regression. This study has three variables: Quality of Service (X1), Quality Products (X2) and the Consumer Satisfaction (Y). This study states that there is significant influence Passenger Service Quality Satisfaction in Indonesian Railways Corporation  (Limited Company) Sub.Divre IV Tanjung Karang. There is a significant influence on the product quality of passenger satisfaction on Indonesian Railways Corporation (Limited Company) Sub.Divre IV Tanjung Karang. Simultaneously, there is significant influence quality of service and product quality to the satisfaction of passengers on Indonesian Railways Corporation (Limited Company) Sub.Divre IV Tanjung Karang with both categories. Keywords: Quality of Service, Product Quality and Passenger Satisfaction